Estoque de carbono em floresta tropical sazonalmente seca - Brandão, Maria Letícia Stefany Monteiro (2023)
Ecosystems are responsible for supporting human life and its diverse activities through the provision of ecosystem services. Seasonally dry tropical forests (SDTFs) are known as one of the main biomes in the world. These environments suffer from anthropogenic activities; deforestation further aggravates the degradation of these ecosystems. One of the problems to be considered about the misuse of land is the emissions of greenhouse gases (GHGs) that directly influence the energy balance of the atmosphere. Therefore, quantifying temporal changes related to biomass and carbon stocks is essential for understanding the dynamics of the carbon cycle in FTTS. The first chapter deals with understanding the behavior of carbon storage in FTTS vegetation, with the general objective of evaluating biomass production and estimating the C stock present in the shrub-tree vegetation of two Caatinga remnants. The second chapter addressed the carbon stock in different compartments, and had the general objective of estimating the necromass (litter and senescent stems) and the carbon stock of different compartments of two Caatinga fragments. The study was carried out at the Vale do Curu Experimental Farm (FEVC) in the municipality of Pentecoste, semiarid region of the state of Ceará. Two areas with different land use were defined, each area with seven permanent plots with dimensions of 10 x 20 m. The quantification of all living and dead shrub-tree plants was carried out, and 10 litter collectors were also allocated in each area. For all the compartments studied (live trees, necromass, and soil), the total C stored in area I was 118.79 Mg ha-1 and 102.68 Mg ha-1 in area II. A difference of 13.5% between the two areas in the year 2022. Regardless of the areas, the largest C stock is stored in the soil. The litter presented the lowest C stock, followed by the tree necromass. Area I, which is in secondary succession for 37 years, has a higher carbon stock than area II under grazing.